Cerebral small vessel disease and systemic arteriopathy in intracranial arterial dolichoectasia patients. (6th November 2018) - Fierini, Fabio; Poggesi, Anna; Salvadori, Emilia; Acquafresca, Manlio; Fainardi, Enrico; Moretti, Marco; Pantoni, Leonardo
Abstract : Objectives: To investigate clinical and demographic characteristics of patients with intracranial arterial dolichoectasia (IADE) and describe the possible coexistence of cerebral small vessel disease (SVD) and systemic arteriopathy. Material and methods: From January 2015 to March 2016, all the patients attending an outpatient service for chronic cerebrovascular diseases were screened for suspected IADE. Identified patients underwent a predefined protocol including: brain MR angiography for the diagnosis of IADE; brain MRI with visual rating of SVD features; whole‐body CT angiography to assess signs of systemic arteriopathy; and neuropsychological examination. Results: Among the 251 patients screened, IADE was diagnosed in seven (mean age ± SD 68.8 ± 7.2 years, six males). Hypertension was the most frequent risk factor. All patients had basilar artery dolichoectasia, two also ectasia of a vessel of the anterior circulation. All patients had white matter hyperintensities that were moderate or severe in six, five had at least one lacune, and all had enlarged perivascular spaces. At least one microbleed was detected in six patients. A variable grade of global cortical atrophy was found in six patients. Systemic arterial ectasia was found in all but one patient. Neuropsychological examination showed a multidomain cognitive impairment in five patients. Conclusions: Our study confirms the high prevalence of cerebral SVD in IADE. The involvement of the brain‐supplying arteries is probably part of a systemic arteriopathy in IADE patients, thus suggesting the usefulness of assessing the whole arterial tree in clinical practice. Cognitive deterioration signs are frequent in these patients.